The impact of restrictive interventions in a learning disability service - Barksby, Justine (2020)
Recent high profile cases have drawn attention to the use of techniques used to control people with learning disabilities when they display challenging behaviour. These techniques are collectively referred to as restrictive interventions in this work and include physical restraint, medication and seclusion.